TANG XIANZU'S (1550-1616) PEONY PAVILION AND TAIZHOU PHILOSOPHY: A PERSPECTIVE FROM INTELLECTUAL HISTORY. (1st May 2013) - Cheng, Yu-Yin
Abstract : This paper explores how intellectual trends, specifically the ideas of the Taizhou movement, of the sixteenth century fostered the rising literary theme of qing . Taking Tang Xianzu's PEONY PAVILION as a case study, the paper first compares Tang's play with its predecessor, a promptbook version circulated in the early sixteenth century, to identify the new ideas that Tang developed in his play; it then traces these ideas back to the Taizhou school's philosophy. The study proposes that the evolution of such seminal ideas as xing (nature), qing (love, or emotions), and li (ritual propriety) within the Taizhou school provided the conceptual bases for Tang to develop his signature play. Sharing with the Taizhou scholars' enthusiasm in public lectures and discussions ( jiangxue ), Tang regarded his drama as another style of jiangxue to convey his idea of qing to a wide audience.